Preparation of expandable flake-graphites with different particle sizes and their flame-retardant application for polypropylene - Hac Thi, Nhung; Nguyen, Thi Thu Hien; Cong Doanh, Truong; Mai Huong, Do Thi; Doan, Tien Dat; Oanh, Ho Thi; Tuyen, Nguyen Duc; Hoang, Mai Ha (Vietnam Journal of Science and Technology, 2024)
Bisulfate intercalated graphites with different particle sizes were prepared by a chemically oxidative method using natural flaky graphites as raw materials. The morphology and structure of the expandable graphites were confirmed by Fourier transform infrared spectroscopy, X-ray diffraction patterns, and scanning electron microscope. The effect of the particle size on the expanded volume was also investigated. Expandable graphite with +100 mesh particle size (EG100) showed the highest expanded volume of 225 mL/g. Moreover, a combination of expandable graphite, red phosphorus (RP), and melamine cyanurate (MC) into a polypropylene (PP) matrix exhibited a synergistic flame retardant effect. The composite loading EG100, RP, and MC with a mass ratio of 1:1:1 and a total filler content of 18 wt.% achieved a UL94 V-0 rating and a limiting oxygen index (LOI) of 28.9 %. The effect of particle size of expandable graphite on the mechanical properties was also evaluated.